RANCANG BANGUN SISTEM MONITORING KONSENTRASI CO2, SUHU, DAN KELEMBABAN PADA PROSES BUDIDAYA JAMUR TIRAM BERBASIS INTERNET OF THINGS - Marbun, David Yoel; Maulana, Eka; Asmungi, Gaguk (Jurnal Mahasiswa TEUB, 2024)
Due to their high nutritional content, oyster mushrooms are a valuable food source with increasing demand. However, increasing oyster mushroom production is challenging because they require specific environmental conditions and cannot grow just anywhere. Therefore, it's crucial to adjust the environmental conditions for optimal oyster mushroom cultivation. Base on the problem, there is a need for a system that can adjust environmental conditions to meet the optimal requirements for oyster mushroom cultivation. Oyster mushrooms typically thrive in highland environments. Several environmental parameters that can influence their growth include CO2 concentration (575-731 ppm), temperature (16˚C to 30˚C), and humidity (80-95%). The designed system is expected to measure these environmental parameters using sensors, include the MQ-135 sensor and the DHT22 sensor.Additionally, actuators will be used to control the environmental parameters and bring them to the desired levels, which is exhaust fan and DC pump. The use of these sensors and actuators will be integrated with an ESP32 microcontroller, which can proces and manage the system. To maximize the quality of the oyster mushrooms, the system will utilize the Internet of Things (IoT), for automated and remote monitoring and control of the oyster mushroom cultivation process through the Blynk application. Keywords: Oyster Mushrooms, ESP32, MQ153, DHT22, Exhaust fan, DC Pump, IoT, Blynk